PENGGUNAAN MEDIA COCOPEAT BEKAS SEBAGAI MEDIA DAUR ULANG TERHADAP PERTUMBUHAN STEK ACACIA CRASSICARPA A. CUNN. EX BENTH DI PELALAWAN CENTRAL NURSERY (PCN)”. - Tuah, Abdul; Mardhiansyah, Mardhiansyah; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
As the raw material of making papers, the need for wood always increases in everyday lives. There is one alternative to overcome that case; it is by advancing woods plants industry (HTI). Accacia crassicarpa is a kind of plant grown for HTI, hence it is necessary for providing a high quality of Accacia crassicarpa seeds and adding some vegetative plants by cutting a tip of leaf. For increasing the productivity, 100% of cocopeat media is used. This research used 100% of ex cocopeat. The problem raised is that the cocopeat media in PCN used only once in nursery so that it becomes a compost heap. Furthermore, in this research ex cocopeat is used as the alternative to fulfill the need for seedling media in PCN, hence the improvement of the quality of ex cocopeat with some tested treatment scientifically is so much required. The aim of this research is to find out the effects of using ex cocopeat as recycle media toward the growth of leaf cutting and determine the finest treatment for seeds growing of Acacia crassicarpa. The research method arranged in complete random program (RAL). The result revealed that using ex cocopeat media with the frying treatment can increase the growth of leaf cutting of Acacia crassicarpa. Fried ex cocopeat media and added with some dolomite are able to show the growth of leaf cutting of the finest Acacia crassicarpa with the living percent (86.66%), bud height (5.52%) and the diameter of leaf cutting (1.37). Keywords : Ex Cocopeat Media, Leaf Cutting, Acacia crassicarpa